2017
DOI: 10.1111/iju.13511
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of fluoroquinolone‐resistant rectal flora in patients undergoing transrectal ultrasound‐guided prostate needle biopsy: A prospective multicenter study

Abstract: These findings suggest that a risk-based approach by history taking cannot predict antibiotic resistance of rectal flora, and physicians should consider targeted antibiotic prophylaxis or extended antibiotic prophylaxis for Korean patients undergoing transrectal ultrasound-guided prostate biopsy because of high antibiotic resistance of rectal flora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
1
16
0
1
Order By: Relevance
“…In this context, we confirmed the infection rate of almost zero of recent single‐centre studies [12,24]. Several groups suggested upfront antibiotic augmentation [7,25], even using carbapenem‐based prophylaxis [26,27], to face the alarming worldwide increase of post‐procedural sepsis following TR biopsies [3–6]. Given the global warnings on antibiotic overuse, the TP biopsy infection rate should be regarded as a major reason to prefer the TP over the TR approach.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this context, we confirmed the infection rate of almost zero of recent single‐centre studies [12,24]. Several groups suggested upfront antibiotic augmentation [7,25], even using carbapenem‐based prophylaxis [26,27], to face the alarming worldwide increase of post‐procedural sepsis following TR biopsies [3–6]. Given the global warnings on antibiotic overuse, the TP biopsy infection rate should be regarded as a major reason to prefer the TP over the TR approach.…”
Section: Discussionsupporting
confidence: 80%
“…Those supporting the TR route argue that it provides superior deliverability in the outpatient setting, and superior patient tolerability in terms of pain, lower rates of urinary retention and shorter procedural timings compared with the TP route [5], whereas those supporting the TP route point to a reduction in the rate of infections, which constitutes a major supporting argument considering the dramatic increase in post-TR-biopsy sepsis rates in recent decades [6,7]. The TP route is also reported to provide greater accessibility to certain areas of the prostate, potentially resulting in higher PCa detection rates [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, many quinolone-resistant bacteria have been reported in Korea and other Asian countries, and the use of quinolone has been reported to cause sole tolerance. [25,26] In addition, we previously reported that the use of third-generation cephalosporins is highly effective in reducing the risk of infectious complications as compared with the use of fluoroquinolone. [27] On the basis of these reports, we also used third-generation cephalosporins in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the study performed by Chung et al, the incidence rates of fluoroquinolone-resistant and extended-spectrum beta-lactamase production were 48.1% and 11.8%, respectively. [26] Recent reports also indicated that targeted antibiotic prophylaxis with rectal-culture screening may have significant benefits. [29] However, performing targeted rectal swab cultures has obvious difficulties depending on regions and institutions, making it clinically inevitable to use empirical antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation